UPAYA MENINGKATKAN PROFESIONALITAS GURU MELALUI PENDAMPINGAN PENULISAN PROPOSAL PENELITIAN TINDAKAN KELAS - Mela Darmayanti; Non Dwishiera Cahya Anasta; Arie Rakmat Riyadi; Effy Mulyasari (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2020)
Classroom Action Research (CAR) is a report of the teacher's real activities in solving problems that occur in teaching and learning activities in the classroom while improving the quality of learning in accordance with the teacher's professional development goals. In fact, UPI PGSD Primary School teachers still encounter difficulties in making PTK proposals as an initial step in fulfilling their professional competencies. Based on this, this study aims to improve the competency of SD PGSD UPI Partner teachers in preparing PTK proposals. The form of activities carried out is assistance with the deductive training model. This research is a quantitative research in the form of a descriptive approach. Data collection was obtained through a questionnaire distributed to 18 PGSD UPI Partner school teachers as mentoring participants. The study began with an identification of the needs of UPI PGSD Primary School SD teachers, followed by assistance in the preparation of the CAR proposal. Assistance materials include CAR in the development of the teaching profession, CAR credit report figures, exploring research problems, and preparing CAR proposals. The results showed an increase in the ability of understanding teachers in preparing PTK proposals.